Database for Forward Dives - Sanders, R.; McClymont, D.; Ferrier, B.; Cornelius, M.; Ordeman, D.; George, S.; Vaughan, A. (coachesinfo.com)
This Database for Forward Dives is Obtained from Analysis of Dives at The FINA Diving World Cup, Wellington, 1999. Content: - Data -Typical Postures - How would you or your diver compare?